Interaction of genotypes and environment for grain yield in upland rice - Silveira, Expedito Paulo; Vencovsky, Roland (Pesquisa Agropecuaria Brasileira, 2014)
With the aim to identify among some released upland rice (Oryza sativa L.) cultivars those best adapted to upland conditions, the genotype x environment interaction for grain yield was studied. Eight genotypes grown in 21 environments in the State of São Paulo, Brazil, were evaluated from 1974 to 1977 seasons. Both genotypes x environments interaction and the variation among the environments showed to be highly significant (P < 0.01 and P < 0.001, respectively). No significant statistical difference between cultivar yields was detected (P < 0.05) and none of the cultivars displayed linear regression coefficient different from unit (P > 0.05). The nonlinear component (sd) was highly significant (P < 0.01) for IAC 25, 'Pratão Precoce' and 'Batatais'; and nonsignificant for IAC 47, IAC 1246, IAC 1131, IAC 5544, and IAC 5032, which are the most stable cultivars, and their response to environmental changes could be predicted. Among the eight cultivars and the ecological conditions tested, these genotypes were the most promising lines toward stable grain production.